2023
DOI: 10.1027/0227-5910/a000832
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Suicide Rate Trends in the Tsunami-Disaster-Affected Area Following the Great East Japan Earthquake

Abstract: Abstract. Background: People who experienced the Great East Japan Earthquake (GEJE) were expected to have additional levels of psychological burden resulting from the stressful conditions imposed during the coronavirus disease 2019 (COVID-19) pandemic; consequently, suicide rates may increase. Aim: We aimed to carry out continuous monitoring of suicide rates in the affected area following the GEJE under COVID-19 pandemic conditions. Method: This descriptive study monitored the suicide rates of the coastal area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…These findings add to the extant literature in that they address how variation in the severity of exposure to pandemic-related stressors across individuals and countries can impact suicide risk. Likewise, these results may shed light on previous findings of a decrease in suicide deaths 7,8 or suicide-related emergency room visits 9 in the early stage of the pandemic. Our findings point to an effect of time, such that chronicity of exposure to pandemic stressors appears to increase the severity of SCS symptoms.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…These findings add to the extant literature in that they address how variation in the severity of exposure to pandemic-related stressors across individuals and countries can impact suicide risk. Likewise, these results may shed light on previous findings of a decrease in suicide deaths 7,8 or suicide-related emergency room visits 9 in the early stage of the pandemic. Our findings point to an effect of time, such that chronicity of exposure to pandemic stressors appears to increase the severity of SCS symptoms.…”
Section: Discussionsupporting
confidence: 66%
“…10 Suicide Risk During the Pandemic Unsurprisingly, a number of studies have shown an increase in suicide risk during the pandemic. 3,7,8 Likewise, in a large (N = 24 378) online, cross-sectional survey study of Chinese university students, mandatory quarantined status was positively associated with self-harm/suicidal ideation (OR = 4.98). 7 Further, in a systematic review by Farooq et al, common contributors to suicidal ideation across international studies included loneliness, financial strain, academic stress related to quarantine, and physical and mental exhaustion, particularly in health care workers.…”
Section: The Suicide Crisis Syndrome (Scs)mentioning
confidence: 99%
See 2 more Smart Citations